2017
DOI: 10.1038/ejhg.2017.126
|View full text |Cite
|
Sign up to set email alerts
|

Third party interpretation of raw genetic data: an ethical exploration

Abstract: In the wake of recent regulations targeting direct-to-consumer genetic testing (DTC-GT), an increasing number of websites have emerged that offer consumers alternative means to derive health information from their DTC-GT raw data. While the ethical concerns associated with DTC-GT have been extensively discussed in the literature, the implications of third party interpretation (TPI) websites have remained largely unexplored. Here we sought to describe these services and elucidate their ethical implications in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…9 These usually work by cross referencing the data against freely available genetic databases and constructing a report based on interpretations in these databases (which may not be up to date). 10 They may report variants and disease risks that were not reported or referred to by the original DTC genetic test company, and might repurpose raw data from tests designed to answer other questions, such as ancestry, to try to provide health information. If a "disease-causing" or "disease-predisposing" genetic variant is found in a person with no medical or family history of the corresponding disease, it may be that there are currently unmeasurable protective genetic (or other) factors in that person's family that mean that the variant is less likely to lead to disease in that person.…”
Section: What Health Information Do Dtc Genetic Tests Provide?mentioning
confidence: 99%
See 1 more Smart Citation
“…9 These usually work by cross referencing the data against freely available genetic databases and constructing a report based on interpretations in these databases (which may not be up to date). 10 They may report variants and disease risks that were not reported or referred to by the original DTC genetic test company, and might repurpose raw data from tests designed to answer other questions, such as ancestry, to try to provide health information. If a "disease-causing" or "disease-predisposing" genetic variant is found in a person with no medical or family history of the corresponding disease, it may be that there are currently unmeasurable protective genetic (or other) factors in that person's family that mean that the variant is less likely to lead to disease in that person.…”
Section: What Health Information Do Dtc Genetic Tests Provide?mentioning
confidence: 99%
“…This is because the "raw data" that such services interpret will contain artefacts, 13 and because the databases used to interpret the data may not be up to date (so might classify variants incorrectly based on outdated evidence). 10 The SNP-chip genotyping method that most DTC genetic tests use is unreliable at testing for very rare disease-causing genetic variants. A recent study looking at BRCA1 and BRCA2 genes in UK Biobank participants found that 96% of disease-causing very rare variants identified by SNP-chip genotyping were false positives.…”
Section: What Health Information Do Dtc Genetic Tests Provide?mentioning
confidence: 99%
“…PGT originally emerged in the United States, but markets are now well established internationally (Borry and Howard 2008;Borry, Cornel, and Howard 2010;Covolo et al 2015;Oliveri et al 2015;Allyse et al 2018;Howard and Borry 2013). More recent developments include the emergence of online portals where consumers can upload their raw data from non-health testing for re-interpretation, generating health-related data; this is known as third party interpretation, or TPI (Badalato, Kalokairinou, and Borry 2017;Wang et al 2018;Metcalfe et al 2019;Nelson, Bowen, and Fullerton 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A great deal has changed in the nutrigenetic (NGX) testing environment since the first NGX tests appeared in the early 2000s. The past two decades have seen exponential growth in the number of genetic testing companies in the market place [1]. As each new genetic testing company appears, it is becoming more and more difficult for the practitioner and consumer to evaluate the credibility of the claims being made and the value of the tests being offered.…”
Section: Introductionmentioning
confidence: 99%